Long-term prognosis of patients with life-threatening ventricular arrhythmias induced by coronary artery spasm. Issue 5 (6th April 2017) - Rodríguez-Mañero, Moisés; Oloriz, Teresa; le Polain de Waroux, Jean-Benoit; Burri, Haran; Kreidieh, Bahij; de Asmundis, Carlos; Arias, Miguel A; Arbelo, Elena; Díaz Fernández, Brais; Fernández-Armenta, Juan; Basterra, Nuria; Izquierdo, María Teresa; et al.
Abstract: Aims: Coronary artery spasm (CAS) is associated with ventricular arrhythmias (VA). Much controversy remains regarding the best therapeutic interventions for this specific patient subset. We aimed to evaluate the clinical outcomes of patients with a history of life-threatening VA due to CAS with various medical interventions, as well as the need for ICD placement in the setting of optimal medical therapy. Methods and results: A multicentre European retrospective survey of patients with VA in the setting of CAS was aggregated and relevant clinical and demographic data was analysed. Forty-nine appropriate patients were identified: 43 (87.8%) presented with VF and 6 (12.2%) with rapid VT. ICD implantation was performed in 44 (89.8%). During follow-up [59 (17–117) months], appropriate ICD shocks were documented in 12. In 8/12 (66.6%) no more ICD therapies were recorded after optimizing calcium channel blocker (CCB) therapy. SCD occurred in one patient without ICD. Treatment with beta-blockers was predictive of appropriate device discharge. Conversely, non-dihydropyridine CCB therapy was significantly protective against VAs. Conclusion: Patients with life-threatening VAs secondary to CAS are at particularly high-risk for recurrence, especially when insufficient medical therapy is administered. Non-dihydropyridine CCBs are capable of suppressing episodes, whereas beta-blocker treatment is predictive of VAs. Ultimately, in spite of medical intervention, some patients exhibited arrhythmogenic events in the long-term, suggesting that ICD implantation may still be indicated for all.